Sistem Informasi Keuangan Sekolah Berbasis User Experience Design - Zahra, Raihana; Munastiwi, Erni (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2025)
User Education in financial information systems has a significant positive impact on the effectiveness and efficiency of system use. Prioritizing user experience in interface design can improve system usability, minimize input errors, and increase user satisfaction. The research method used in this research uses a qualitative approach. Data collection techniques in this research are through interviews and observations by asking questions to respondents to obtain information and an overview of the problems being studied. In this research, the data source obtained came from interviews with respondents. By observing an intuitive layout, easy navigation, and good responsiveness, users can access the necessary financial information quickly and efficiently. Improved User Education also allows users to make remote payments. Additionally, focusing on user experience aspects can reduce the training burden for new users, minimize input errors, and increase user acceptance of system changes.